The Relationship Between Eating Habits with the Gastritis at the Medical Faculty Level of Student 2010 Sam Ratulangi University Manado - Pasaribu, Margareth Piesesha; Lampus, Benedictus S.; Sapulete, Margareth (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Impact of globalization and technological development are two possible causes for the shift in the lifestyle of students. Confirms previous findings that lifestyle affects one's eating habits. Lifestyle and eating habits identified a factor that affects the occurrence of the gastritis. Through lifestyle changes such as diet and diet often consume fast food and spicy, not eating or delay, lack of physical activity, alcohol consumption, use of tobacco, drugs, stress and infection Helicobacter py-lori affects the stomach lining, causing the gastritis. The current study was conducted to analyze the relationship between eating habits with the gastritis at the medical faculty level of student 2010 Sam Ratulangi University Manado. This research is an analytical cross - sectional studies design. Sample pieces in this research were 74 student respondents were already included in the criteria. Results showed that the majority of respondents (58.1%) had a high meal frequency (â‰¥ 3 times a day), the majority of respondents (64.9%) consume large amounts of food (> 1 scoop rice), the next 51.4% re-spondents were in the category of frequently consumed foods and beverages are not irritating. Results of Chi - Square showed that there was no significant association between the frequency of eating with the gastritis (p = 0.177), there was no significant relationship between the meal portion with the gastritis (p = 0.854), there was no significant relationship between the type of food and beverages with the gastritis (p = 0.010). There is no relationship between the frequency of eating with the gastritis. There is no relationship between the meal portion with the gastritis. There is a relationship be-tween the type of food and beverages with the gastritis.Keywords: frequency of eating, meal portion, foods and beverages, gastritis